(untitled) (Journal of Pakistan Orthopaedic Association, 2021)
Objective: To determine the outcome of percutaneous endoscopic interlaminar lumbar discectomy for prolapsed intervertebral disc in terms of pain reduction and functional disability. Methods: This descriptive study was conducted in Department of Orthopaedics & Spine Surgery Hayat Abad medical complex Peshawar from 3rd October 2018 to 3rd December 2020.All patients with lumbar disc prolapse fulfilling the inclusion criteria were operated with percutaneous full endoscopic interlaminar lumbar discectomy. Post operative back pain and leg pain was assessed with Visual Analogue Scale(VAS) and functional disability with Oswestry Disability Index (ODI) questionnaire at 2nd week,3rd month and 6th months. Preoperative VAS and ODI was compared with post operative VAS and ODI and P value was calculated with independent-sample t test for statistical significance. P value <0.05 was considered significant. Results: A total of 50 patients including 31 (62%) males and 19 (38%) females with a mean age of 37.10±7.95 years were included in this study. The VAS for back pain and leg pain improved from pre operative 4.68±2.01 and 7.44±1.47 to 0.90±1.61 and 0.74±1.30 respectively at 6th months follow up(P <0.05). The mean ODI score improved from pre operative 34.4±7 36±4 to 5.3±2 post operative at 6th month( P < 0.05). Conclusion: Percutaneous endoscopic lumbar discectomy for prolapsed intervertebral disc is an effective alternative to open discectomy as it resulted in significant pain reduction and minimum functional disability in our patients.